Developing Bilateral and Spatial Concepts in Primary School-aged Children: An Empirical Evaluation of the Anker Bilateral Spatial System - Janet E. Richmond PhD; Myra Taylor PhD, JP; Sarah Evans (Scholarworks @ WMU, 2014)
Background: Visual-spatial and visual-motor perceptual difficulties contribute to school-aged learning problems. Hence, a need exists to address children's visual-spatial and visual-motor perceptual difficulties as early as possible in the child's school career. Thus, this study reports on the evaluation of the Anker Bilateral Spatial System's (ABSS) effectiveness in remediating primary school children's perceptual difficulties. Method: Thirty-one children (17 boys and 14 girls) aged 6 to 12 years who had been identified by their classroom teacher as having observable visual-spatial and visual-motor perceptual difficulties participated in a 10-week pre/posttest intervention study. The study's pre/posttest assessments included the Developmental Test of Visual-Motor Integration (VMI), the Spatial Awareness Skills Program Test (SASP), and two subscales of the School Function Assessment (SFA). Results: Paired t-test statistics were calculated on the pre/post intervention scores. Paired t-test statistics calculated (p = .05) that significant change had occurred in the writing speed (t = -3.978, p < .001). Conclusion: Given that the study's Year 1 students made progress in more areas of remediation than did any other year level, it is evident that the ABSS is particularly effective with this year group.